Oncothermia principles and practices - Szasz, Andras; Szasz, Nora.; Szasz, Oliver; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Oncothermia is the next generation medical innovation that delivers selective, controlled and deep energy for cancer treatment. The basic principles for oncothermia stem from oncological hyperthermia, the oldest approach to treating cancer. Nevertheless, hyperthermia has been wrought with significant controversy, mostly stemming from shortcomings of controlled energy delivery. Oncothermia has been able to overcome these insufficiencies and prove to be a controlled, safe and efficacious treatment option. This book is the first attempt to elucidate the theory and practice of oncothermia, based on rigorous mathematical and biophysical analysis, not centered on the temperature increase. It is supported by numerous in-vitro and in-vivo findings and twenty years of clinical experience. This book will help scientists, researchers and medical practitioners in understanding the scientific and conceptual underpinnings of oncothermia and will add another valuable tool in the fight against cancer. Professor Andras Szasz is the inventor of oncothermia and the Head of St Istvan University's Biotechnics Department in Hungary. He has published over 300 papers and lectured at various universities around the world. Dr. Oliver Szasz is the managing director of Oncotherm, the global manufacturer and distributor of medical devices for cancer treatment used in Europe & Asia since the late 1980s. Dr. Nora Szasz is currently a management consultant in healthcare for McKinsey & Co.
1. Oncology treatments and their limits -- 2. Hyperthermia results and Challenges -- 3. Thermo-bio-physics -- 4. Oncothermia ? New kind of Oncologic Hyperthermia -- 5. Acknowledgement -- 6. References.
Electronic reproduction.
Keywords: Cancer -- Thermotherapy; Electromagnetism -- Physiological effect; Heat -- Physiological effect; Clinical biochemistry; Electronic books